Tools for analysis of large-scale networks (I) algorithms, analytics and visualization - Chua, Chee Ann (2017)
Data is a valuable asset, but only for people who have adequate skills of data mining and apply them to analyze and reveal the trends or patterns that are hidden inside the otherwise unstructured data. This project aimed to create a tool that is able to help the user to gain insights from a large-scale dataset by applying multiple data mining processes on the data and visualizing the results. Among all the social media sites, Twitter was chosen and 500 million raw tweets were used as the dataset in this project. Only some part of the information from the tweets would be extracted for analysis, specifically, geo-coordinates, timestamp, and the tweet content itself.